АНТИЧКА И РИМСКО-РОМЕЈСКА МАКЕДОНИЈА – РИЗНИЦА НА ПОЛИТИКОЛОШКИ КАТЕГОРИИ ВО СВЕТСКАТА ИСТОРИЈА (Филологические заметки, 2019)
While summering up historical references, only the exclusive conclusions which support the thesis will be conveyed – that the Macedonian history is distinctive and individual, and different and foreign in relation to the so called history of the Hellenes. Fortunately, these exclusive inferences are “first class” – this is witnessed by eminent persons from the Hellenic genus, intellectuals, rhetorical philosophers, rhetors, and the most distinguished politicians of just that time, the time before the very demise of the Hellenic city-states, and right before the magnificent rise of Macedonia. The main historical impression is that: on one side is the historical sphere of the “joint defeat of all the Hellenes” and “deprivation of destiny of their famous city-states”, on the other, again, is – the separate history of the rise and glory of the antique Macedonians, their rulers, of the world basilea of Alexander of Macedonia. These two spheres are joint, as much as they are utterly opposed in their historic co-relation. Actually, the historical conditions are changing from the root, even the sharp border between the Hellenes and the barbarians, among whom are, of course, also the Macedonians, is disappearing, a process of cultural and social symbiosis comes about, according to which, Philip is the carrier of the exclusive idea for a global society. Understandably, these ideological aspirations do not come forth peacefully, because they are not only about a cultural “globalization”, but about a political one that must be carried out through war and fighting. So, such important material imposes a need for rereading history. The critical understanding of the contemporary conception of the humanities strives for diversity and differentness, for particularity and cultural equality: local investigation of the history is promoted, hierarchical assessment of cultures is refused, traditional prejudices about “high” and “low” cultures are being rejected, favouring particular historical peoples, states, cultures, on account of the already neglected peoples and cultures, is disregarded. It is well known that the “pet” of world historiography is classical Helada, and that its favourites are the Hellenic culture and Roman civilization. Traditional historiography not only disregards other nations and cultures, but it is also assigns them all to the general denominator of just these two cultures. It goes without saying that ancient Greek culture and Roman civilization are the dominant focus of world history, but the “word” of the ancient Greek and Roman historians, logographers, doxographers, must not be uncritically accepted; right here, one should “catch” the ancient Greek writers, who very often, in accordance with their xenophobic mentality, make sense of the world as divided into “domestic” and “foreign”, Hellenes and barbarians, into “battles between themselves” and “wars with foreigners” (Plato, Republic). However, - why does the momentous historiographic illusion of recent times happen – the unique historical phenomenon, the epoch of the Macedonian pambasilea, the most exclusive event in the history of the old continents, the idea of the ecumenical state and one unified civilization, to be called “Hellenism”! “Hellenism”, even though in that historical period, the most renowned Hellenic city-states are already entering the zone of the historical and cultural margin, contrary to the new world centers in Egypt and in the East, which are being founded by Alexander of Macedon and are being named by him as Alexandrides; so why not call this epoch “Alexandrism”, or “Macedonism” in accordance with the only carriers of this civilization – the Macedonian rulers.